Design of a new hydrokinetic turbine simulation model based on the extended power coefficient concept - Manuel Rico-Secades; Antonio Javier Calleja-Rodríguez; Aitor Fernández-Jiménez; Eduardo Álvarez-Álvarez; Fher Said Macedo-Garcia; Jaime Arau-Roffiel (International Journal of Electrical Power & Energy Systems)
The operation of hydrokinetic turbines under blockage conditions causes situations where the classical power coefficient does not adequately explain their energy extraction, often exceeding Betz’s limit, as it is referred only to the kinetic energy of the water flow in open field or without boundaries. The research presented defines the extended power coefficient as the fraction of the energy available, including kinetic and potential energy, obtained by the turbine in a rectangular water channel. The physical limits of the energy extraction are also determined. Even, a methodology has been developed to dynamically find the values of the extended power coefficient according to the blockage produced in the channel.Moreover, and based on this extended coefficient, a hydrokinetic turbine simulation model is presented to be applied in cases of flow blockage instead of the actual models of the electrical simulators based in the classical coefficient. The new simulation model has been validated through experimental tests with a micro-hydrokinetic turbine operating in a low-speed hydrodynamic tunnel. The design has been implemented in the LTSpice tool and tested allowing to obtain turbine operation data such as power produced, torque or rotational speed.